\(a,=\dfrac{\sqrt{x}-8+5}{\sqrt{x}-8}=1+\dfrac{5}{\sqrt{x}-8}\in Z\\ \Leftrightarrow\sqrt{x}-8\inƯ\left(5\right)=\left\{-5;-1;1;5\right\}\\ \Leftrightarrow\sqrt{x}\in\left\{3;7;9;13\right\}\\ \Leftrightarrow x\in\left\{9;49;81;169\right\}\left(tm\right)\\ b,=\dfrac{\sqrt{x}-2+7}{\sqrt{x}-2}=1+\dfrac{7}{\sqrt{x}-2}\in Z\\ \Leftrightarrow\sqrt{x}-2\inƯ\left(7\right)=\left\{-1;1;7\right\}\left(\sqrt{x}-2>-2\right)\\ \Leftrightarrow\sqrt{x}\in\left\{1;3;9\right\}\\ \Leftrightarrow x\in\left\{1;9;81\right\}\\ c,=\dfrac{2\left(\sqrt{x}+3\right)+2}{\sqrt{x}+3}=2+\dfrac{2}{\sqrt{x}+3}\in Z\\ \Leftrightarrow\sqrt{x}+3\inƯ\left(2\right)=\varnothing\left(\sqrt{x}+3>3\right)\\ \Leftrightarrow x\in\varnothing\)